Let's analyze the rewritten equation step by step:
You started with the equation:
\[ 5x + 3x + 6 = 4(2x + 6) \]
You then simplified the left side:
\[ 8x + 6 = 4(2x + 6) \]
Next, you simplified the right side:
\[ 8x + 6 = 8x + 24 \]
Now, let's work with the simplified equation:
\[ 8x + 6 = 8x + 24 \]
If we try to isolate \( x \) by subtracting \( 8x \) from both sides, we get:
\[ 6 = 24 \]
This is a contradiction, as 6 does not equal 24.
This indicates that there are no values of \( x \) that would satisfy the original equation.
Therefore, the conclusion is:
No solutions.